2019
DOI: 10.1016/j.bbalip.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte-specific lysosomal acid lipase deficiency protects mice from diet-induced obesity but promotes hepatic inflammation

Abstract: Lysosomal acid lipase (LAL) hydrolyzes cholesteryl esters (CE) and triglycerides (TG) to generate fatty acids (FA) and cholesterol. LAL deficiency (LAL-D) in both humans and mice leads to hepatomegaly, hypercholesterolemia, and shortened life span. Despite its essential role in lysosomal neutral lipid catabolism, the cell type-specific contribution of LAL to disease progression is still elusive. To investigate the role of LAL in the liver in more detail and to exclude the contribution of LAL in macrophages, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…As LIPA was shown to be a direct target of miR-125b-5p [48], we postulate that exosome-delivered miR-125b-5p represses LIPA in M1 macrophages. Consistently with our findings, LIPA deficiency and miR-125 overexpression in macrophages both induce identical pathways regulating proinflammatory factors and myeloid cell recruitment [29,30,49,50]. Correspondingly, LIPA knockout in melanoma-associated myeloid cells promotes cancer cell proliferation and metastasis [51].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As LIPA was shown to be a direct target of miR-125b-5p [48], we postulate that exosome-delivered miR-125b-5p represses LIPA in M1 macrophages. Consistently with our findings, LIPA deficiency and miR-125 overexpression in macrophages both induce identical pathways regulating proinflammatory factors and myeloid cell recruitment [29,30,49,50]. Correspondingly, LIPA knockout in melanoma-associated myeloid cells promotes cancer cell proliferation and metastasis [51].…”
Section: Discussionsupporting
confidence: 89%
“…M1 macrophages treated with exosomes showed a decreased expression of genes involved in lipid catabolic processes, including LIPA ( Figure 6C). Because others have already described that LIPA deficiency induces a proinflammatory phenotype in macrophages and hepatocytes [27][28][29][30], we analyzed if miR-125b-5p represses LIPA. The overexpression of miR-125b-5p mimics in M1 polarized macrophages strongly reduces LIPA protein compared to M1 macrophages transfected with control mimics ( Figure 6D).…”
Section: Mir-125b-5p Targets Lysosomal Acid Lipase a (Lipa)mentioning
confidence: 99%
See 1 more Smart Citation
“…The identification and characterization of such acid lipase(s) will provide important insights into the endosomal/lysosomal lipid-sorting machinery. In the course of preparing this study, similar results on the phenotypes of mice lacking LAL in hepatocytes were reported by Leopold et al (44), and our report expands the characterization of the remnant, non-LAL acid hydrolytic activity in liver.…”
Section: Discussionsupporting
confidence: 90%
“…In conflict with this potential paradigm, animal studies suggest that the liver is the most physiologically important contributor to the increased de novo cholesterol biosynthesis in LALD [18]. Indeed, liver-specific LIPA deficiency is associated with dyslipidemia and increased cholesteryl ester storage [19]. Restoration of LAL activity through virusmediated transduction or transgenics in mouse models of LALD and liver-transplantation in LALD patients has proven beneficial [11,[20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%